Investigating Speaking Skill’s Problems and Difficulties that Encounter Secondary Schools’ Students in Riyadh City - Ibrahim, Abdelraziq Abdelghani Mahil (Journal of Educational and Psychological Sciences, 2017)
This study aimed at investigating the Speaking Skill’s Problems and Difficulties that Encounter Secondary Schools’ Students in Saudi Arabia in Riyadh City. The scope of the study was in the area of the applied linguistics. The objectives of this study were: to investigate the difficulties and the problems that face secondary school students in speaking English, to draw teachers’ attention to the importance of speaking skills, to encourage speaking skill among the students, and to offer recommendations that might help teachers and students to overcome and reduce these speaking problems and difficulties. The study has adopted the descriptive analytical method. The sample of the study consisted of (20) male teachers in Riyadh city in the second semester of the academic year 1437 / 1438 H. A questionnaire was designed as a tool to collect the data. The study used a recent statistical package to analyze the data. The results indicated Saud secondary schools students face problems and difficulties in speaking skill. To conclude, the researcher gives the following recommendations: English text books should be well prepared to motivate and encourage students to speak the language and they should be given enough time to practice speaking skills, schools should be provided with language labs or at least with some educational techniques, so as to introduce classroom communication activities in good and interesting manners, and teachers should offer extra speaking skill activities in order to enable students to speak fluently.